The Effect of Music Album Visuals on Brand Marketing Strategy Case Study "MITO" DPR Ian . Album - Florencine, Celia Regina; Kurniawan, Ferren Valerie; Fortuna, Ivania; Setiabudi, Miranda (Jurnal VICIDI, 2022)
In this modern era, the influence of marketing strategy is very important to improve a brand image. Marketing strategies are certainly carried out in various ways and in various media. One of them is the visual influence of a brand or product that can be remembered and can increase brand awareness to the audience. This study was conducted based on a case study of the music album “MITO” by DPR IAN which has a unique visual concept. This study also aims to determine the importance of visual influence on the marketing of a brand or product. The research method of this study was carried out based on primary data, namely quantitatively through surveys distributed to the audience according to the target market on one of the social media platforms and based on secondary data obtained from several journals and articles.